A Prey-Predator Model with a Reserved Area - Dubey, B. (Nonlinear Analysis: Modelling and Control, 2007)
In this paper, a mathematical model is proposed and analysed to study the dynamics of a prey-predator model. It is assumed that the habitat is divided into two zones, namely free zone and reserved zone. Predators are not allowed to enter into the reserved zone. Criteria for the coexistence of predator-prey are obtained. The role of reserved zone is investigated and it is shown that the reserve zone has a stabilizing effect on predator-prey interactions.